2021
DOI: 10.3390/molecules26082234
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Gallium-Modified ZSM-5 for Conversion of Light Hydrocarbons

Abstract: Light olefins are key components of modern chemical industry and are feedstocks for the production of many commodity chemicals widely used in our daily life. It would be of great economic significance to convert light alkanes, produced during the refining of crude oil or extracted during the processing of natural gas selectively to value-added products, such as light alkenes, aromatic hydrocarbons, etc., through catalytic dehydrogenation. Among various catalysts developed, Ga-modified ZSM-5-based catalysts exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 134 publications
(231 reference statements)
1
19
0
Order By: Relevance
“…The reaction mechanism for alkane dehydrogenation has been discussed by several research groups. 53,56,76–78 Lercher et al theoretically investigated the PDH mechanism on pairs of Ga + cations and BASs via the formation of [GaH] 2+ ions and reported the experimental activation enthalpy for PDH to be 106 kJ mol −1 . 53 Bell et al showed in a recent theoretical study for EDH that [GaH] 2+ and [GaH 2 ] + ions are more plausible catalytically active sites than Ga + cations and proposed the following reaction mechanisms: alkyl or carbenium mechanism on [GaH] 2+ ions, and alkyl or concerted mechanism on [GaH 2 ] + ions.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction mechanism for alkane dehydrogenation has been discussed by several research groups. 53,56,76–78 Lercher et al theoretically investigated the PDH mechanism on pairs of Ga + cations and BASs via the formation of [GaH] 2+ ions and reported the experimental activation enthalpy for PDH to be 106 kJ mol −1 . 53 Bell et al showed in a recent theoretical study for EDH that [GaH] 2+ and [GaH 2 ] + ions are more plausible catalytically active sites than Ga + cations and proposed the following reaction mechanisms: alkyl or carbenium mechanism on [GaH] 2+ ions, and alkyl or concerted mechanism on [GaH 2 ] + ions.…”
Section: Resultsmentioning
confidence: 99%
“…We have considered a specific T-site for the insertion of the Ni 2+ site based on previous works. [63][64][65] We have also considered a cluster model representative of the current system in accordance with previous works. 66,67 The adsorption energies point out that the exothermicity of the adsorption of the aromatic molecules primarily depends on the type of site upon which it is adsorbing, and such molecules adsorb more strongly over Ni 2+ /acid than over zeolite acid sites.…”
Section: Direct Molecular-level Characterization Of the Total Coke An...mentioning
confidence: 99%
“…[13][14][15][16] Various metals such as Mo, Co, Zn, and Ga have been loaded on MFI-type zeolites to improve the catalytic activity for EDA reactions. [17][18][19][20][21][22] Among these catalysts, Zn-doped MFI-type zeolite (ZnZSM-5) has been reported as an active catalyst for producing BTX from ethane. 9 It is known that Zn 2+ ions located on ion-exchange sites are active sites for dehydrogenation and dehydroaromatization in EDA reactions.…”
Section: Introductionmentioning
confidence: 99%